Environmental causes of between-population difference in growth rate of a high-altitude lizard - Lu, Hong-Liang (BMC Ecol, 2018)
BACKGROUND: Ectothermic animals living in cold (high latitude or high elevation) regions are predicted to grow slower due to limited thermal opportunities for activity and food resources than those living in warm regions. However, the Qinghai toad-headed lizards (Phrynocephalus vlangalii) grow faster and reach a larger adult size at a high-elevation site than at a low-elevation site. In this study, we aimed to identify the genetic and environmental causes of this between-population difference in growth rate by conducting mark-recapture and common garden experiments on juvenile growth rate, and investigating the thermal environment, lizard body temperature, potential prey availability at the two elevation sites. RESULTS: Compared with low-elevation individuals, high-elevation juvenile lizards had higher growth rates in the field, but grew at similar rates in the laboratory. High-elevation lizards had higher active body temperatures than low-elevation lizards despite similar air temperatures in the period of field investigation. The high-elevation site had relatively more and larger preys than the low-elevation site. CONCLUSIONS: Inter-population difference in growth rate of P. vlangalii may primarily result from developmental plasticity in response to the difference in environmental resources, rather than genetic differentiation. The higher growth rate of high-elevation lizards is likely associated with higher potential food availability and higher active body temperatures.